2014
DOI: 10.1186/1475-2859-13-50
|View full text |Cite
|
Sign up to set email alerts
|

Production of recombinant protein by a novel oxygen-induced system in Escherichia coli

Abstract: BackgroundThe SoxRS regulon of E. coli is activated in response to elevated dissolved oxygen concentration likely to protect the bacteria from possible oxygen damage. The soxS expression can be increased up to 16 fold, making it a possible candidate for recombinant protein expression. Compared with the existing induction approaches, oxygen induction is advantageous because it does not involve addition or depletion of growth factors or nutrients, addition of chemical inducers or temperature changes that can aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Successful development of expression systems rely on the availability of well characterized promoters with suitable properties. For industrial applications, it is desirable that promoters can be induced by mechanisms that do not rely on the addition of a chemical agent, , shifts of pH or temperature . Oxygen limitation is an attractive means of inducing the expression of genes of interest.…”
mentioning
confidence: 99%
“…Successful development of expression systems rely on the availability of well characterized promoters with suitable properties. For industrial applications, it is desirable that promoters can be induced by mechanisms that do not rely on the addition of a chemical agent, , shifts of pH or temperature . Oxygen limitation is an attractive means of inducing the expression of genes of interest.…”
mentioning
confidence: 99%
“…On the contrary, an increased concentration of oxygen would stress the microbial cells due to generation of toxic products, such as superoxide ( O2 - ), and produced in increased levels under elevated oxygen concentrations 6. These toxic products are more reactive than the molecular oxygen 26 and can provoke series of metabolic changes in the microbial cells such as oxidation of important macromolecules like protein and DNA oxidation 34. Therefore, a sufficient oxygen supply is crucial to microbial cells growth and to avoid detrimental effects of oxygen concentrations above and below the optimal concentration.…”
Section: Resultsmentioning
confidence: 99%
“…As the oxygen level is above the critical concentration, the specific uptake rate is constant and microbial cells are not starved. Generally, 5–10 % of the air saturation is considered the value of critical oxygen level under the average working conditions and it can be varied depending on the microbial species 26. In shaking flasks, the rate of oxygen transfer ( OTR ) is calculated from Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Joseph Shiloach (National Institute of Diabetes Digestive and Kidney Disease/NIH, USA) reported an example of how oxidative stress faced by cells during growth can be exploited for the production of heterologous proteins. He showed that in response to high oxygen concentrations, soxS expression increased 16-fold in E. coli, making its promoter a possible candidate for inducing recombinant protein expression under these conditions [11]. Induction of recombinant protein expression by increasing the dissolved oxygen concentration was found to be a simple and efficient alternative expression strategy that excludes the use of chemical, nutrient or thermal inducers that have a potential negative effect on cell growth or on product recovery.…”
Section: Microbial Stress In Industrial Production Processesmentioning
confidence: 99%